Child maintenance in Malaysia: are the amounts sufficient? - Rokiah Kadir; Safiek Mokhlis; Junaidah Abd Karim; Fauziah Abu Hasan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Typical child maintenance issues following divorces included custodial mothers not having maintenance orders, fathers not paying the amounts ordered, or the amounts ordered far too low to maintain the children at subsistent level despite the fathers affording to pay more. Insufficient amount of maintenance can affect children’s protection and upbringing. The determination of whether the amounts of maintenance ordered by courts were sufficient to maintain the children at subsistent level has not been extensively explored so far. This study aimed at answering this question by analysing, with specific focus on age categories of children, how much has been claimed in child maintenance and how much has been granted by the Syariah courts. The study also analysed maintenance orders in comparison with the typically most important factor in child maintenance cases, i.e., fathers’ incomes. Whilst existing research cases been more focused on only selected decisions, and largely reported only on the amounts granted in court orders, this study analysed all child maintenance cases, and adopted a descriptive, non-conventional method by profiling quantitative details of decisions, which is necessary since child maintenance amounts are decided on case-by-case basis, with judges exercising broad discretion. The findings showed that, over the 50-year period, amounts claimed by mothers and amounts ordered by the courts kept increasing, but, despite the increase, the amounts ordered so far were still small and insufficient based on the current cost of living. The finding may be of assistance to family law practitioners, judges, and parents seeking more thorough information on the assessment issue of child maintenance. The findings should also provide awareness to child poverty economic analysis in future, particularly for policy responses and implications.